Tinjauan Siyasah Dusturiyah Terkait Hukuman Mati Berdasarkan UU No. 1 Tahun 2023 KUHP - Nurhafiza Nurhafiza; Ridho Alamsyah; Aisyah Alwiyah; Muhammad Razi Asarwani (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
The death penalty is the heaviest punishment in history which since the existence of Ham the death penalty has begun to be criticized and is no longer applied. However, some Islamic countries still apply the death penalty for convicts with serious cases. Basically, Islamic teachings come first compared to the principles and principles in Duham, which raises the pros and cons in society as well as society in countries with the most Muslims but are democratic countries. This research is a normative research in which the author examines Law No. 1 of 2023 Criminal Code on conditional death penalty. Islamic perspective is also presented in looking at this regulation. This research uses library research techniques by using materials in the form of books and journals as well as Law No. 1 of 2023 Criminal Code. The results of this study indicate that the death penalty is very contrary to the principle of Ham, namely the right to life, also in Islam this must be minimized because Islam is also a religion that protects the soul.